Divergent lineages in two species of Dendrobium orchids (D. speciosum and D. tetragonum) correspond to major geographical breaks in eastern Australia. (17th June 2013) - Burke, Jacinta M.; Ladiges, Pauline Y.; Batty, Erin L.; Adams, Peter B.; Bayly, Michael J.; Katinas, Liliana
Abstract Aim We investigated genetic divergence among two widespread eastern Australian orchids (Dendrobium sect. Dendrocoryne): Dendrobium speciosum and Dendrobium tetragonum. These orchids are endemic to mesic habitats, with distributional ranges that cross major geographical breaks associated with deep divergences in various fauna. We compared the biogeography of these orchids with other taxa and tested for congruence of divergence date estimations. Location Eastern Australia, latitude 14° S to 34° S. Methods Phylogenetic relationships within each species were estimated using maximum parsimony based on sequences of internal transcribed spacer (ITS) regions of nuclear ribosomal DNA and the psbA–trnH spacer region of plastid DNA. Divergence dates were inferred by Bayesian relaxed‐clock dating, calibrated on an early Miocene macrofossil, Dendrobium winikaphyllum from New Zealand. Results Deep divergences were revealed within each species. Dendrobium speciosum includes three major geographical clades (deepest 2.6% ITS divergence): a northern Queensland clade, which occurs mainly to the north of the Black Mountain Corridor (BMC) in the Wet Tropics; a central Queensland clade; and a southern clade related to the central clade and separated from it by a dry corridor, the St Lawrence Gap (SLG). The central and northern lineages show overlap near the BMC. Divergence in this area is estimated to date from the Pliocene, possibly late Miocene, 4.3 (2.0–6.9) Ma, and at the SLG in the early Pleistocene, possibly late Pliocene, 2.0 (0.6–3.8) Ma. Dendrobium tetragonum also includes two clades, deeply divergent (3%) at the SLG, estimated as Pliocene in age but possibly latest Miocene, 3.7 (1.8–5.9) Ma. Main conclusions Dendrobium orchids reveal significant divergence associated with geographical breaks in eastern Australia, the SLG and BMC, patterns broadly concordant with findings for fauna. We infer that divergences were driven by topographical and climatic conditions, with contraction and fragmentation of mesic biomes during periods of drying in the late Neogene.